Peer support and shared decision making in Open Dialogue: Opportunities and recommendations - Chmielowska, Marta; Mannocci, Nell; Tansel, Alexander; Zisman-Ilani, Yaara (Frontiers in Psychology, 2022)
Open Dialogue (OD) is a person-centred social network model of crisis and continuing mental healthcare, which promotes agency and long-term recovery in mental illness. Peer support workers (PSWs) who have lived experience of mental illness play a key role in OD in the UK, as they enhance shared understanding of mental health crisis as part of the OD model and provide a sense of belonging and social inclusion. These elements are in alignment with the shared decision making (SDM) approach in mental health, which focuses on person-centred communication in treatment decision-making. The previously documented benefits of peer-led SDM include increased engagement with services, symptom reduction, increased employment opportunities, and reduced utilisation of mental and general health services. While the contribution of peer support and SDM principles to OD has been acknowledged, there is only a small body of literature surrounding this development, and little guidance on how peer support can enhance treatment decision-making and other aspects of OD. This viewpoint, which was co-authored by people with lived experience of mental illness, clinicians, and researchers, discusses practical implications and recommendations for research and training for the provision of a co-produced OD model grounded in peer support and SDM.